Polyamines protect boar sperm from oxidative stress in vitro. (5th March 2022) - Li, Rongnan; Wu, Xiaodong; Zhu, Zhendong; Lv, Yinghua; Zheng, Yi; Lu, Hongzhao; Zhou, Kaifeng; Wu, De; Zeng, Wenxian; Dong, Wuzi; Zhang, Tao
Abstract: Sperm are susceptible to excessive reactive oxygen species (ROS ). Spermine and spermidine are secreted in large amounts by the prostate and potent natural free radical scavengers and protect cells against redox disorder. Thus, we used boar sperm as a model to study the polyamines uptake and elucidate whether polyamines protected sperm from ROS stress. Seven mature and fertile Duroc boars (aged 15 to 30 mo) were used in this study. In experiment 1, spermine and spermidine (3.6 ± 0.3 and 3.3 ± 0.2 mmol/L, respectively) were abundant in seminal plasma, and the content of polyamine decreased ( P < 0.05) after preservation at 17 °C for 7 d or incubation at 37 °C for 6 h. In experiment 2, using labeling of spermine or spermidine by conjugation with fluorescein isothiocyanate and ultra-high-performance liquid chromatography, we found that the accumulation of spermine or spermidine in sperm was inhibited by quinidine and dl -tetrahydropalmatine (THP, organic cation transporters [OCT ] inhibitors, P < 0.05), but not mildronate and l -carnitine (organic cation/carnitine transporter [OCTN ] inhibitors, P > 0.05). In experiment 3, the addition of spermine or spermidine (0.5 mmol/L) in the extender resulted in higher motility, plasma membrane and acrosome integrity, and lower ROS level after preservation in vitro at 17 °C for 7 d ( P < 0.05). In experiment 4, in the condition of oxidative stress (treatment with H2 O2 at 37 °C for 2 h), the addition of spermine (1 mmol/L) or spermidine (0.5 mmol/L) in extender increased activities of glutathione peroxidase, glutathione reductase, and glutathione S-transferase; reduced glutathione and oxidized glutathione ratio ( P < 0.05); and alleviate oxidative stress-induced lipid peroxidation, DNA damage, mitochondrial membrane potential (ΔΨm ) decline, adenosine triphosphate depletion, and intracellular calcium concentration ([Ca 2+ ]i ) overload ( P < 0.05), thereby improving boar sperm motility, the integrity of plasma membrane and acrosome ( P < 0.05) in vitro. These data suggest that spermine and spermidine alleviate oxidative stress via the antioxidant capacity, thereby improving the efficacy of boar semen preservation. Lay Summary: Boar semen preservation and artificial insemination are widely used in the pig industry. Although preservation in vitro prolongs sperm lifespan, reactive oxidative species (ROS ) also accumulate in sperm with the increased preservation period. ROS over-accumulation would impair motility, the integrity of plasma membrane and acrosome, mitochondrial function, and eventually lead to infertility. Spermine and spermidine are secreted in large amounts by the prostate and are potent natural free radical scavengers. Thus, we used boar sperm as a model to study the polyamines uptake and elucidate whether polyamines protected sperm from ROS stress. We found for the first time that organic cation transporters mediated polyamines uptake in sperm cells, and that extracellular polyamines decreased during preservation in vitro. The addition of polyamines increased the activities of glutathione-related antioxidant enzymes and reduced glutathione and oxidized glutathione ratio, and alleviate oxidative stress-induced mitochondrial dysfunction, lipid peroxidation, and DNA damage, thereby maintaining sperm quality in vitro. These data suggest that spermine and spermidine alleviate oxidative stress, thereby improving the efficacy of boar semen preservation. Abstract : Spermine and spermidine that are secreted in large amounts by the prostate alleviate oxidative stress, thereby improving the efficacy of boar semen preservation.